2010
DOI: 10.1021/jp911259n
|View full text |Cite
|
Sign up to set email alerts
|

Sessile-Water-Droplet Contact Angle Dependence on Adsorption at the Solid−Liquid Interface

Abstract: We investigate both analytically and experimentally the possible role of line tension in determining the contact angle of sessile water droplets on a polished Cu substrate. In a closed system with constraints that make the Helmholtz function the thermodynamic potential, the curvature of the three-phase line and the height of an axisymmetric droplet on its center line could be measured. The adsorption on each of the surfaces used to construct the experimental chamber was taken into account, and the value of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…Regarding the first phenomenon, it has been reported that a small tip‐to‐substrate distance combined with a 1:2 inner‐to‐outer tip diameters ratio cause the formation of larger meniscus, and as a result, a larger deposition area . Similarly, the larger base size can be attributed to a small tip‐to‐substrate distance and approach speed, as well as to the hydrophilic nature of Cu …”
Section: Resultsmentioning
confidence: 99%
“…Regarding the first phenomenon, it has been reported that a small tip‐to‐substrate distance combined with a 1:2 inner‐to‐outer tip diameters ratio cause the formation of larger meniscus, and as a result, a larger deposition area . Similarly, the larger base size can be attributed to a small tip‐to‐substrate distance and approach speed, as well as to the hydrophilic nature of Cu …”
Section: Resultsmentioning
confidence: 99%
“…Solid tensions are not typically accessible to tensiometry (at least not without additional theory [14, 210] and the inevitable assumptions/simplifications embodied therein). Also, interpretation of solid interfacial tensions almost always depends on the reliability of the Young equation, which is of dubious merit for reasons mentioned in Section 6.1.…”
Section: 0 Energy and Mass Balance In Protein Adsorptionmentioning
confidence: 99%
“…1 (color online). In each experiment, an evaporating water droplet with a three-phase-line radius of 9 AE 0:01 mm was maintained on a polished Cu substrate (roughness 53 nm [19]) and in steady state by a syringe pump that injected deionized, degassed water into the droplet base through a small (0.6-mm-diameter) tube at the same rate that vapor was removed from the enclosing chamber. The droplet height and the temperature in the liquid and vapor phases were measured with a U-shaped thermocouple (25 m bead diameter) that was mounted on a positioning micrometer.…”
mentioning
confidence: 99%
“…If zð0Þ and C cl are known, but the evaporation ignored, the contact angle of an equivalently sized equilibrium droplet e may be determined by the methods described in [19]. The values of e correlate with , but are always less, Table I. The pressures in the liquid and vapor phases at the interface were obtained as part of the procedure to predict the droplet shape, and the temperatures in each phase at 10 points along the interface were measured.…”
mentioning
confidence: 99%